Treating Protein Misfolding Diseases: Therapeutic Successes Against Systemic Amyloidoses - Nevone, Alice; Merlini, Giampaolo; Nuvolone, Mario (Frontiers in Pharmacology, 2020)
Misfolding and extracellular deposition of proteins is the hallmark of a heterogeneous group of conditions collectively termed protein misfolding and deposition diseases or amyloidoses. These include both localized(e.g.Alzheimer’s disease, prion diseases, type 2 diabetes mellitus) and systemic amyloidoses. Historically regarded as a group of maladies with limited, even inexistent, therapeutic options, some forms of systemic amyloidoses have recently witnessed a series of unparalleled therapeutic successes, positively impacting on their natural history and sometimes even on their incidence. In this review article we will revisit the most relevant of these accomplishments. Collectively, current evidence converges towards a crucial role of an early and conspicuous reduction or stabilization of the amyloid-forming protein in its native conformation. Such an approach can reduce disease incidence in at risk individuals, limit organ function deterioration, promote organ function recovery, improve quality of life and extend survival in diseased subjects. Therapeutic success achieved in these forms of systemic amyloidoses may guide the research on other protein misfolding and deposition diseases for which effective etiologic therapeutic options are still absent.